Migration and modernities : the state of being stateless, 1750-1850 - DeLucia, JoEllen; Shields, Juliet, 1976- (Edinburgh : Edinburgh University Press, 2019)
This collection initiates transnational, transcultural and interdisciplinary conversations about migration in the 18th and 19th centuries.
Introduction : a literary history of migration, 1750--1850 / JoEllen DeLucia and Juliet Shields -- 1. Moving voices : competing perspectives on migration -- Byron's ambivalent modernity : touring and forced migration in Don Juan / Betsy Bolton -- Diasporas : Thomas Pringle and Mary Prince / Kenneth McNeil -- Transatlantic masculinites : military leadership and migration in the South American wars of independence / M. Soledad Caballero -- At home on the prairie? Black hawk, Margaret Fuller, and American Indian dispossession / Melissa Adams-Campbell -- 2. Migrants as cultural mediators : epistemes and aesthetics of mobility -- "An alien to my country" : migration and statelessness in Frances Burney's The Wandere / Patricia Cove -- The great migration and individual travels : precursors of Serbian modernity? / Dragana GrbcÌ¹ -- Orientalism in the transit : company men, colonial historiography, and other handmaidens of empire / Olivera Jokic -- The Turkish refugee as vagrant slave : spaces of disconnection and dispossession in Ishmael Bashaw's refugee narrative / Claire Gallien.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Online resource; title from home page (viewed on August 16, 2019).
JSTOR
Keywords: Emigration and immigration in literature; Immigrants in literature; Colonization in literature; English literature -- 18th century -- History and criticism; English literature -- 19th century -- History and criticism; American literature -- 18th century -- History and criticism; American literature -- 19th century -- History and criticism; Émigration et immigration dans la littérature.; Immigrants dans la littérature.; Colonisation dans la littérature.; Littérature anglaise -- 18e siècle -- Histoire et critique; Littérature anglaise -- 19e siècle -- Histoire et critique; Littérature américaine -- 18e siècle -- Histoire et critique; Littérature américaine -- 19e siècle -- Histoire et critique; HISTORY / Modern / 18th Century; American literature; Colonization in literature; Emigration and immigration in literature; English literature; Immigrants in literature; 1700-1899; Criticism, interpretation, etc